Transtorno dismórfico corporal sob a ótica do cirurgião plástico brasileiro - Ribeiro, Fernanda Dias (2019)
Body dysmorphic disorder from Brazilian plastic surgeon’s optic. On a scenario where the reinless search for beauty ideals is observed, associated with the ascending panorama of plastic surgery, the body dysmorphic disorder (BDD) stands out as a psychiatric disorder of high prevalence between patients that seek for cosmetic treatments, frequently serious, underdiagnosed and underreported. The BDD is defined as an excessive preoccupation about a minimal or imperceptive flaw for other people. That excessive concern causes significative clinical suffering or social, occupational or any other important functioning area impairment. The BDD is also associated with poor quality of life, which may lead to high rates of suicidal ideation and even to suicide attempt. In this context, the importance of awareness and knowledge by plastic surgeons is evident. The present study aimed to analyze if Brazilian plastic surgeons are aware of how important body dysmorphic disorder is in their practice; identify if Brazilian plastic surgeons investigate the presence of BDD in their patients prior to surgery, and verify the reasons why they do not; and to access how Brazilian plastic surgeons proceed when they suspect the presence of BDD. This is a cross-sectional, observational, prospective study with quantitative approach. It was applied a semi-structured online questionnaire on a sample of 6.078 plastic surgeons, after ethical and administrative approvals, as to provide an answer for the proposed goal. The main findings were a responders population constituted of 160 specialists, mainly male (63,7%) and young (70% being younger than 45 years old), and about half of the sample with less than 11 years of graduation and board-certification. Regarding the routine of asking for psychiatric evaluation, 23,7% of the plastic surgeons have said that they never do. As the awareness about BDD, only 9,4% of the participants have said to be familiar with the clinical characteristics of the disorder and 13,1% found themselves updated with diagnostic criteria, and 18,1% had no knowledge about them. It is observed that the investigation about image disorders is made invariably in only 18,8% of the cases and only 8,8% (14 individuals) are acquainted with any early diagnosis instruments of the disorder. Furthermore, even with 56,2% believing that BDD is an absolute contraindication for aesthetic surgery, and 57,5% assuming that they do not perform the surgery when they identify the presence of DBB, 80% of the sample have performed some kind of procedure on patients with the disorder, only lately suspecting the condition. In addition, about 41% of the doctors have suffered some kind of threat from these patients. Therefore, it was concluded that Brazilian plastic surgeons have limited awareness about the importance of BDD in their practice; that they rarely investigate the presence of this disorder in their patients before operating on them, mainly because of the lack of awareness to the clinical characteristics of the disorder and the lack of knowledge about screening instruments; and when faced with an eventual suspicion of BDD, these professionals tend not to treat or refer these patients to a specialized follow-up. On the other hand, 95% of the interviewed sample have interest in educational activities that can allow to overcome this disturbing reality